Pengembangan Media Edukatif SliMotion untuk Pembelajaran Seni Tari Kelas III Sekolah Dasar - Azzahra, Fatimah; da Ary, Deasylina (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2025)
This study addresses the limited variety of engaging learning resources for teaching dance in elementary schools by developing SliMotion, an educational medium designed for third-grade students within the topic of movement and expression. The development process followed the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), integrating a board game and flashcards to encourage creativity, motivation, and active participation in learning dance. Data collection involved questionnaires validated by one content expert, one media expert, one practitioner, and trials conducted with 17 students. Data were analyzed using both qualitative descriptive and quantitative approaches. Validation results showed an average score of 3.65, categorized as very valid, with feasibility ratings above 92% from experts and practitioners. Student responses indicated high practicality at 93.2%, confirming that the medium is effective and easy to implement. The findings demonstrate that SliMotion provides an innovative and enjoyable alternative to conventional methods, significantly improving student engagement and learning outcomes. The originality of this research lies in integrating board game mechanics with expressive dance education, a rarely explored combination. This contribution highlights the potential of gamified media to enrich elementary arts education and promote interactive, student-centered learning.